PRODUCTION OF THE PLAN FOR CONTINUING HEALTHEDUCATION: REPORT OF AN EXPERIENCE IN THE WESTERN REGION OF THE STATE OF SANTA CATARINA - Carine Vendruscolo; Denise Zocche; Altamir Trevisan Dutra (Universidade Federal do Paraná, 2015)
Report of the experience of elaboration of the Plano de Ações Regionais de Educação Permanente em Saúde (regional action plan for continuing health education) in the western macro-region of the state of Santa Catarina, in 2014, by representatives of health and education managers, health workers, educational institutions and social control - the four elements (quadrilateral) of training. Twenty-six (26) cities of the region participated in the workshop, being represented by the segments that compose the Comissão de Integração Ensino Serviço- CIES (commission for integrating teaching and service). After the end of the activities of the groups, the participants gathered in a plenary meeting for the approval of the proposals submitted. It should be stressed the scarce representativeness of social control in each of the cities, the presence of municipal secretaries of education and the participation of the nursing profession, representing the educational institutions. The experience corroborated the assumptions of the quadrilateral, and the discussions provided significant opportunities for new meetings, translating the complexity, the wealth and the power of Continuing Education movements.